FAKTOR YANG BERPENGARUH TERHADAP KOMPETENSI ENTREPRENEUR - Sidharta, Helena; Saputra, Ruswiati Surya; B. Ismail, Noor Azizi (UNUSA Press, 2018)
Entrepreneurial competence is an important variable that affects the success of an entrepreneur. Factors affecting entrepreneurial competence need to be researched because of strong competence needed by an entrepreneur to achieve success. Based on the literature study, education, entrepreneurial personality and parenting style are indicated to influence entrepreneurial competence. Further studies show that entrepreneurial personality and parenting style require further research because the relationship between these two variables and entrepreneurial competence needs to be understood more deeply. The result of this research is proposition development to further test the relationship between entrepreneurial personality, parenting style, and entrepreneurial competence. Furthermore, based on indicators used in previous studies, testing is suggested using structural equation modeling (SEM) because entrepreneurial personality is measured using Big Five Personality and entrepreneurial competence is measured using indicators from Man & Lau (2000) so that the indicators of both variables included in the unobserved variabl